Thermodynamic properties of solutions of the acrylic acid in 1,2-dichloroethane and acetic acid - Serheyev, Valentyn; Kos, Yuri; Van-Chin-Syan, Yuri (Publishing House of Lviv Polytechnic National University, 2011)
The saturated vapor pressure of the acrylic acid solutions in 1,2-dichloroethane and acetic acid was measured by static tensimetric method in the temperature range of 295 to 355 K. The composition of the equilibrium phases as well as the activity coefficients (γ1 and γ2) were received from the experimental measurements of the temperature-dependent saturated vapor pressure. Then we used the temperature and concentration dependent activity coefficients to calculate the excess thermodynamic functions of the solutions mixing (HE, GE, SE). Статичним тензиметричним методом виміряний тиск насиченої пари над розчинами акрилової кислоти в 1,2-дихлоретані та оцтовій кислоті в температурному інтервалі 295–355 К. За даними температурної залежності тиску насиченої пари розраховано склад рівноважних фаз та коефіцієнти активності компонентів. За температурною та концентраційною залежністю коефіцієнтів активності розраховані надлишкові термодинамічні функції змішування досліджених розчинів (HE, GE, SE).
Термодинамічні властивості розчинів акриловової кислоти в 1,2-дихлоретані та оцтовій кислоті
Keywords: acrylic acid; saturated vapor pressure; vapor-liquid equilibrium; activity coefficients; яexcess thermodynamic functions of mixing; акрилова кислота; тиск насиченої пари; рівновага рідина-пара; коефіцієнти активності; надлишкові термодинамічні функції змішуванн